Knowledge Level of Calories and BMI of the Students of the National University of Malaysia - Zainordin, Nadzirah Hanis; Budiningsari, Dwi; Jalambo, Marwan; Wali, Hamzah; Sivaji, Ashok; Choon, Ooi Theng; Emmanuel, Haruna; Mani, Suresh; Omar, Baharudin (Pakistan Journal of Nutrition, 2015)
The aim of this study was to determine the knowledge level of calories and body mass index (BMI) among students in the Faculty of Health Science (FHS), National University of Malaysia. This comprises of studying of the interactions and relationships between independent variables such as type of schools, age, BMI, education level, gender and family history of non-communicable diseases with the outcome variable of interest being knowledge score among subjects. To achieve this, an online questionnaire-based survey was conducted among students from different schools at FHS, National University of Malaysia (n = 179), regarding knowledge of calories and BMI. The results showed that only 10.6 % of subjects were able to obtained high scores (>70%). Overall, students from FHS had a poor knowledge on calories and BMI, with a lower mean score of knowledge (52.53±13.79) than expected score of 70%. Two-way analysis of variance showed that subjects from School of Healthcare obtained a significant higher score as compared to School of Diagnostic and Applied Health Sciences and School of Rehabilitation Sciences; while scores was lower among Malays as compared to non-Malays. However, the interaction between these two factors were not significant (p = 0.911). Binary logistic regression analysis revealed significant association between education level and knowledge on calories and BMI (p<0.01; β = 15.31); however, for the age, BMI, race, gender and family history of diseases, the association were not significant.